The Great Escape:Health, Wealth, and the Origins of Inequality - ANGUS DEATON (Princeton University Press, 2013)
LIFE IS BETTER NOW than at almost any time in history. More people are richer and fewer people live in dire poverty. Lives are longer and parents no longer routinely watch a quarter of their children die. Yet millions still experience the horrors of destitution and of premature death. The world is hugely unequal. Inequality is often a consequence of progress. Not everyone gets rich at the same time, and not everyone gets immediate access to the latest life-saving measures, whether access to clean water, to vaccines, or to new drugs for preventing heart disease. Inequalities in turn affect progress. This can be good; Indian children see what education can do and go to school too. It can be bad if the winners try to stop others from following them, pulling up the ladders behind them. The newly rich may use their wealth to infl uence politicians to restrict public education or health care that they themselves do not need. This book tells stories of how things got better, how and why progress happened, and the subsequent interplay of progress and inequality. The Great Escape, a famous movie about prisoners of war in World War II, is based on the exploits of Roger Bushell (in the fi lm, Roger Bartlett, played by Richard Attenborough), a South African in the Royal Air Force who was shot down behind German lines, and who repeatedly escaped and was repeatedly recaptured.1 In his third attempt, as depicted in the fi lm—the Great Escape—250 prisoners escaped with him through tunnels dug from Stalag Luft III. The movie tells the story of how the escape was planned; the ingenuity that went into constructing three tunnels, Tom, Dick, and Harry; and the improvisation and technical skills that went into making civilian clothes and forging papers, all under the eyes of the watchful guards. All but three of the POWs were eventually recaptured, and Bushell himself was executed on direct orders from Hitler. Yet the emphasis of the movie is not on the limited success of this particular escape, but on man’s unquenchable desire for freedom, even under impossibly diffi cult circumstances.